Long-term resource utilisation and associated costs of exercise during (neo)adjuvant oncological treatment: the Phys-Can project. (3rd July 2022) - Ax, Anna-Karin; Husberg, Magnus; Johansson, Birgitta; Demmelmaier, Ingrid; Berntsen, Sveinung; Sjövall, Katarina; Börjeson, Sussanne; Nordin, Karin; Davidson, Thomas
Abstract: Background: Exercise during oncological treatment is beneficial to patient health and can counteract the side effects of treatment. Knowledge of the societal costs associated with an exercise intervention, however, is limited. The aims of the present study were to evaluate the long-term resource utilisation and societal costs of an exercise intervention conducted during (neo)adjuvant oncological treatment in a randomised control trial (RCT) versus usual care (UC), and to compare high-intensity (HI) versus low-to-moderate intensity (LMI) exercise in the RCT. Methods: We used data from the Physical Training and Cancer (Phys-Can) project. In the RCT, 577 participants were randomised to HI or to LMI of combined endurance and resistance training for 6 months, during oncological treatment. The project also included 89 participants with UC in a longitudinal observational study. We measured at baseline and after 18 months. Resource utilisation and costs of the exercise intervention, health care, and productivity loss were compared using analyses of covariance (RCT vs. UC) and t test (HI vs. LMI). Results: Complete data were available for 619 participants (RCT HI: n  = 269, LMI: n  = 265, and UC: n  = 85). We found no difference in total societal costs between the exercise intervention groups in the RCT and UC. However, participants in the RCT had lower rates of disability pension days ( p < .001), corresponding costs ( p = .001), and pharmacy costs ( p = .018) than the UC group. Nor did we find differences in resource utilisation or costs between HI and LMI exercise int the RCT. Conclusion: Our study showed no difference in total societal costs between the comprehensive exercise intervention and UC or between the exercise intensities. This suggests that exercise, with its well-documented health benefits during oncological treatment, produces neither additional costs nor savings.